Improving collaboration in the implementation of global biodiversity conventions. Issue 4 (8th February 2019) - Rogalla von Bieberstein, Katharina; Sattout, Elsa; Christensen, Mads; Pisupati, Balakrishna; Burgess, Neil D.; Harrison, Jerry; Geldmann, Jonas
Abstract: Eight conventions make up the biodiversity cluster of multilateral environmental agreements (MEAs) that provide the critical international legal framework for the conservation and sustainable use of nature. However, concerns about the rate of implementation of the conventions at the national level have triggered discussions about the effectiveness of these MEAs in halting the loss of biodiversity. Two main concerns have emerged: lack of capacity and resources and lack of coherence in implementing multiple conventions. We focused on the latter and considered the mechanisms by which international conventions are translated into national policy. Specifically, we examined how the Strategic Plan for Biodiversity 2011–2020 and the associated Aichi Biodiversity Targets have functioned as a unifying grand plan for biodiversity conservation. This strategic plan has been used to coordinate and align targets to promote and enable more effective implementation across all biodiversity‐related conventions. Results of a survey of 139 key stakeholders from 88 countries suggests streamlining across ministries and agencies, improved coordination mechanisms with all relevant stakeholders, and better knowledge sharing between conventions could improve cooperation among biodiversity‐related conventions. The roadmap for improving synergies among conventions agreed to at the 13th Convention on Biological Diversity's Conference of Parties in 2016 includes actions such as mechanisms to avoid duplication in national reporting and monitoring on conventions and capacity building related to information and knowledge sharing. We suggest the scientific community can actively engage and contribute to the policy process by establishing a science‐policy platform to address knowledge gaps; improving data gathering, reporting, and monitoring; developing indicators that adequately support implementation of national plans and strategies; and providing evidence‐based recommendations to policy makers. The latter will be particularly important as 2020 approaches and work to develop a new biodiversity agenda for the next decade is beginning. Abstract : Article impact statement : To strengthen the global biodiversity conventions, the scientific community needs to engage in enhancing cooperation among them. Abstract : Mejora en la Colaboración en la Implementación de las Convenciones Mundiales sobre la Biodiversidad Resumen: Ocho convenciones son las que forman la agrupación multilateral de acuerdos ambientales (MEAs, en inglés), los cuales proporcionan el marco de trabajo legal importante para la conservación y el uso sustentable de la naturaleza. Sin embargo, la preocupación por la tasa de implementación de estas convenciones a nivel nacional ha disparado discusiones sobre la efectividad de estas MEAs para detener la pérdida de la biodiversidad. Han surgido dos preocupaciones principales: la falta de capacidad y recursos y la falta de coherencia en la implementación de múltiples convenciones. Nos enfocamos en la segunda y consideramos los mecanismos mediante los cuales las convenciones internacionales se transforman en reglamentos y políticas nacionales. En específico, examinamos cómo el Plan Estratégico para la Biodiversidad 2011 – 2020 y los Objetivos de Biodiversidad de Aichi asociados han funcionado como un gran plan unificador para la conservación de la biodiversidad. Este plan estratégico se ha usado para coordinar y alinear los objetivos para promover y habilitar una implementación más efectiva a lo largo de todas las convenciones relacionadas con la biodiversidad. Los resultados de una encuesta entre 139 accionistas clave de 88 países sugieren la optimización en los ministerios y en las agencias, una coordinación mejorada de los mecanismos entre todos los accionistas relevantes, y una mejor partición del conocimiento entre las convenciones podría aumentar la cooperación entre las convenciones relacionadas con la biodiversidad. La hoja de ruta para mejorar las sinergias entre las convenciones, acordada en la Conferencia de Participantes de la 13 ra Convención sobre la Diversidad Biológica en 2016, incluye acciones como los mecanismos para evitar la duplicación de reportes y monitoreos nacionales sobre las convenciones y la capacidad de construcción relacionada con la partición de la información y el conocimiento. Sugerimos que la comunidad científica pueda participar activamente y contribuir al proceso de políticas al establecer una plataforma política‐científica que resuelva los vacíos en el conocimiento; mejore la recolección, reporte y monitoreo de datos, desarrolle indicadores que respalden adecuadamente a la implementación de planes y estrategias nacionales; y proporcione recomendaciones basadas en evidencia para los políticos. La última acción será de particular importancia conforme se aproxima el 2020 y se inicie la labor por desarrollar una nueva agenda de biodiversidad para la siguiente década. 摘要: 八项多边环境协定中关于生物多样性的公约为自然的保护和可持续利用提供了重要的国际法律框架。然而, 对这些公约在国家层面执行情况的担忧已经引发了关于多边环境协定能否有效阻止生物多样性丧失的讨论。其中主要存在两个问题: 能力和资源的不足, 以及多项公约的执行缺乏连贯性。我们重点关注后者, 并分析了国际公约向国家政策转化的机制。具体来说, 我们研究了《2011‐2020 年生物多样性战略规划》及相应的爱知生物多样性目标是如何作为一个整体统一的生物多样性保护计划发挥作用的。这一战略规划被用于协调和统一各项目标, 以促进和实现所有与生物多样性相关的公约更有效的实施。对来自 88 个国家 139 个主要利益相关者的调查表明, 要提高生物多样性相关的公约之间的合作, 需要精简各部委和机构, 改进利益相关者之间的协调机制, 并推动公约之间更好的知识共享。 2016 年《生物多样性公约》第十三次缔约国会议商定的加强公约间协作的路线图中, 包括了避免重复对公约进行国家报告工作和监督检查的机制、发展信息与知识共享能力等行动。我们建议, 科学界可以通过建立科学–政策平台来弥补知识空缺; 加强数据的收集、报告和监督; 制定充分支持国家规划和战略实施的指标; 为决策者提供基于证据的建议等途径来积极参与并促进政策过程。随着 2020 年的临近, 为下一个十年制定新的生物多样性议程的工作也已经开始, 这一点将尤为重要。[翻译: 胡怡思; 审校: 聂永刚]